(untitled) (Papeles, 2023)
This article outlines the actions that the Ministry of Equality, Gender and Diversity in Santa Fe province has developed since it was established founding in 2020. After doing research on the institutional history of gender in Santa Fe province, this article discusses the policies developed and implemented addressing gender equality. On the other hand, it reflects on the obstacles that remain to be overcome on this topic. The analysis is carried out by taking into account the main principles that are followed by the Ministry to design its public policies -institutionality, territoriality and transversality- This will be is done considering the theoretical framework of the gender mainstream. The main question is: Does the existence of a Ministry of Equality, Gender and Diversity allow for giving answers to the demands related to gender inequalities? What is the provincial government of Santa Fe doing in this regard? In the future, what will the challenges be?